Empowering landless women through collectives in the agrifood systems: A review - Mohammed, Kamaldeen; Najjar, Dina (International Center for Agricultural Research in the Dry Areas, 2023)
Collectives are viewed as agents for women's economic empowerment in the Agrifood System through collective action. Globally, women constitute about 36% of employed people in AFS and almost half of the workforce in the food processing and services sector. As such, empowering women in the agrifood systems is a vital prerequisite for fostering a fair and peaceful world as well as enhancing women’s income and wellbeing. This review explores how collectives can empower vulnerable and often landless women in the agri-food sector. The review highlights the types of collectives, the level of formality and how that affects women’s participation in collectives. Broadly, the role of collectives in women empowerment can be described as being economical, social or political empowerment. However, for a full and effective empowerment of women, there must be an enabling ecosystem of formal laws, rules and regulations and informal social norms, religious beliefs and customs favouring collectivization. There also need to be favourable socio-economic and cultural factors that allow for women's ability and willingness to collectivize. Women collectives can potentially improve women’s income-earning opportunities, access to financial resources, and other social outcomes. However, collectives still face challenges such as inadequate access to productive resources, insufficient participation of women in decision-making, structural and cultural gender constraints, and the overburden of collectives with women empowerment.